Perspectives for Sustainable Aviation Biofuels in Brazil - Luís A. B. Cortez; Francisco E. B. Nigro; Luiz A. H. Nogueira; André M. Nassar; Heitor Cantarella; Márcia A. F. D. Moraes; Rodrigo L. V. Leal; Telma T. Franco; Ulf F. Schuchardt; Ricardo Baldassin Junior (International Journal of Aerospace Engineering)
The aviation industry has set ambitious goals to reduce carbon emissions in coming decades. The strategy involves the use of sustainable biofuels, aiming to achieve benefits from environmental, social, and economic perspectives. In this context, Brazilian conditions are favorable, with a mature agroindustry that regularly produces automotive biofuel largely adopted by Brazilian road vehicles, while air transportation has been growing at an accelerating pace and a modern aircraft industry is in place. This paper presents the main conclusions and recommendations from a broad assessment of the technological, economic, and sustainability challenges and opportunities associated with the development of drop-in aviation biofuels in Brazil. It was written by a research team that prepared the initial reports and conducted eight workshops with the active participation of more than 30 stakeholders encompassing the private sector, government institutions, NGOs, and academia. The main outcome was a set of guidelines for establishing a new biofuels industry, including recommendations for (a) filling the identified research and development knowledge gaps in the production of sustainable feedstock; (b) overcoming the barriers in conversion technology, including scaling-up issues; (c) promoting greater involvement and interaction between private and government stakeholders; and (d) creating a national strategy to promote the development of aviation biofuels.